IMPLEMENTASI PERATURAN DAERAH KOTA SURABAYA NOMOR 7 TAHUN 2002 TENTANG KEBIJAKAN RUANG TERBUKA HIJAU (Studi Kasus Kebun Bibit Bratang Kota Surabaya) - Indriyani, Ika; Indartuti, Endang; Soenarjanto, Bagoes (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
The municipal government policy on the utilization of green open spaces in Surabaya is stated in Local Regulation No. 7 of 2002 on the management of green open spaces. The law also states that green open space is a city space that serves as a green area of city park, green forest area of the city, green area of urban recreation, green area of cemetery, green agricultural area, green area of green line, and green area of yard Utilization of green open space Such as flora and fauna parks in Surabaya or commonly referred to as Bratang Bratang Surabaya gardens are the answer of this polluted metro-politan city, although the state of Bratang seedlings is still poorly maintained and has become a dispute between private parties and the municipal authorities.Problem Formulation in this Research is How Implementation of Local Regulation of Surabaya City Number 7 Year 2002 About Green Open Space Policy of Bratang Seed Garden? This research also aim to to know Implementation of Local Regulation of Surabaya City Number 7 Year 2002 In Green Open Space Policy of Bratang Seed Garden. This research is descriptive research using qualitative approach. Technique of collecting data is done by observation, interview, and documentation.The informant of research in this research is Kasubag TU UPTD Rekreasi DKRTH and Satgas Bratang Seed Garden. The data validity check is done by triangulation of source and method.From the research results can be seen that the implementation of the implementation of the policy of Regulation No 7 of 2002 is considered effective and goes well. The result of this research is by connecting from George Edward III theory that is from communication aspect, resources, disposition, and bureaucratic structure.Â Keywords: Policy, Implementation, Qualitative, Theory George Edward III